EFEKTIVITAS PENERAPAN DIGITAL MARKETING DALAM UPAYA MENINGKATKAN PENDAPATAN UKM KULINER DI LUBUK PAKAM - Rahma, Nazela Aulia; Adlina, Hafiza (Jurnal Ekonomi Kreatif dan Manajemen Bisnis Digital, 2024)
The implementation of digital marketing aims to utilize the potential of digital media as a means to increase business visibility, reach a wider target market, build interactions with customers, and ultimately increase the revenue of MSMEs. The purpose of this study is to identify and analyze the strategies and forms of digital marketing implementation carried out by culinary MSMEs and their impact on business revenue growth. This research adopts a qualitative approach, with data collection methods including observation, interviews, and documentation. The results of this study indicate that the implementation of digital marketing by culinary MSMEs in Lubuk Pakam has made a significant contribution, with an increase in revenue of approximately 47%. Through the use of social media, delivery services, as well as promotions, discounts, and giveaways, MSMEs are able to expand their market reach and attract potential consumers.